1992
DOI: 10.1016/0896-8411(92)90001-7
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of αβ T lymphocytes in the nervous system in experimental autoimmune encephalomyelitis: Its possible implications for recovery and acquired tolerance

Abstract: We have recently shown that apoptosis, an active process of cellular self-destruction, occurs in the central nervous system in Lewis rats with acute experimental autoimmune encephalomyelitis (EAE) induced by inoculation with myelin basic protein (MBP) and adjuvants. Conventional light and electron microscopic studies suggested that some of the apoptotic cells were oligodendrocytes and that others were hematogenous mono-nuclear cells. To determine whether any of the apoptotic cells were T lymphocytes, we used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 35 publications
8
55
1
Order By: Relevance
“…Therefore we suggest that apoptotic deletion of T cells in GBM is due to activationinduced apoptosis following antigen presentation by glioma cells and microglia. This mechanism is similar to that which has been suggested to account for apoptosis of autoreactive T cells in the CNS during spontaneous recovery from experimental autoimmune encephalomyelitis, where astrocytes and microglia may act as non-professional antigenpresenting cells (Pender, 1999 andPender andRist, 2001). Our hypothesis that T-cell apoptosis in GBM results from overstimulation of the T-cell receptor in the absence of appropriate costimulation is consistent with the findings of Prins et al (2001) who showed that tumour-infiltrating lymphocytes functioned poorly when tested in vitro, with decreased proliferative activity and other characteristics of defective T cells.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Therefore we suggest that apoptotic deletion of T cells in GBM is due to activationinduced apoptosis following antigen presentation by glioma cells and microglia. This mechanism is similar to that which has been suggested to account for apoptosis of autoreactive T cells in the CNS during spontaneous recovery from experimental autoimmune encephalomyelitis, where astrocytes and microglia may act as non-professional antigenpresenting cells (Pender, 1999 andPender andRist, 2001). Our hypothesis that T-cell apoptosis in GBM results from overstimulation of the T-cell receptor in the absence of appropriate costimulation is consistent with the findings of Prins et al (2001) who showed that tumour-infiltrating lymphocytes functioned poorly when tested in vitro, with decreased proliferative activity and other characteristics of defective T cells.…”
Section: Discussionsupporting
confidence: 72%
“…T-cell apoptosis has been identified as a critical process in recovery from immune-mediated CNS damage (Pender et al, 1992, Tabi et al, 1994and Pender and Rist, 2001. Apoptotic T cells in the CNS are phagocytosed by macrophages, microglia, astrocytes and oligodendrocytes (Nguyen andMagnus et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During spontaneous recovery from MBP-EAE, there is apoptosis of T cells (Pender et al, 1991 andPender et al, 1992;Schmied et al, 1993) and macrophages/microglia in the CNS (Nguyen et al, 1994;White et al, 1998a). There is selective apoptosis of V 8.2 + MBP-reactive T cells (Tabi et al, 1994 andTabi et al, 1995;McCombe et al, 1996a), which may be due to CD95-mediated antigen-specific activation-induced apoptosis (White et al, 1998b).…”
Section: Discussionmentioning
confidence: 99%
“…The relapsing disease produced by treatment with CsA may result from the suppression of the immunoregulatory mechanisms that normally prevent further episodes of disease. In EAE, such regulatory mechanisms may include suppressor cells (Karpus et al, 1992), downregulatory cytokines, and apoptosis of T cells in the central nervous system (CNS) (Pender et al, 1991 andPender et al, 1992;Schmied et al, 1993;Tabi et al, 1994 andTabi et al, 1995;McCombe et al, 1996a). …”
Section: Introductionmentioning
confidence: 99%